Smuggling destruction - Clare Perry (Our Planet, 2018)
It was a warm July day in 1997 when a fax arrived at the London headquarters of refrigerant company Trans-Cool Trading from a Chinese chemicals supplier. It was sent in response to an enquiry about the possibility of importing banned chlorofluorocarbons (CFCs) into Europe.